Implementation of Goods and Services Procurement Policy Through SIPLah in Vocational High School Educational Units in West Jakarta - Diah Kartika Sari; Deddy Supriady; Agung Edi Rustanto; Harits Hijrah Wicaksana (International Publisher (YAPENBI), 2024)
The implementation of the goods and services procurement policy through SIPLah at the SMK level education units in West Jakarta shows significant progress in an effort to create a more efficient and transparent procurement system. The implementation of SIPLah is supported by a clear organizational structure with a structured division of roles, starting from the Ministry of Education and Culture at the central level to the education unit. The school principal acts as the main decision-maker and person in charge of the program, assisted by the treasurer and BOSP team members for technical implementation. This research uses a descriptive qualitative approach with data collection through interviews with informants using George C. Edward III's Theory . The results showed that the implementation of goods and services procurement through SIPLah in vocational education units in West Jakarta has had a positive impact in increasing transparency and accountability in the procurement of goods and services in education units. Overall, the implementation of SIPLah has gone well in terms of administrative and operational aspects. However, continuous evaluation and development are still needed, especially in the aspects of improving human resource competencies, optimizing system integration, and improving price control mechanisms. Despite some obstacles, the high commitment of all stakeholders has created a conducive environment for the successful implementation of SIPLah.